2020
DOI: 10.1111/mec.15710
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of pathogenicLeptospirainfection with greater abundance and co‐occurrence of rodent hosts across a counter‐urbanizing landscape

Abstract: Land use change can elevate disease risk by creating conditions beneficial to species that carry zoonotic pathogens. Observations of concordant global trends in increased pathogen prevalence or disease incidence and landscape change have generated concerns that urbanization could increase transmission risk of some pathogens. Yet host-pathogen relationships underlying transmission risk have not been well characterized within cities, even where contact between humans and species capable of transmitting pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 121 publications
2
7
0
Order By: Relevance
“…The reverse was not found, suggesting that the potential for transmission is asymmetric. Consistent with this, signatures of directional transmission have been found for bacterial symbionts among co-occurring rodent host species [12,19]. We also detected several viruses in multiple host species, which is consistent with trends indicating that viruses exhibit less host specificity than bacterial symbionts [31].…”
Section: Patterns Of Viral Assemblage Structuresupporting
confidence: 89%
See 2 more Smart Citations
“…The reverse was not found, suggesting that the potential for transmission is asymmetric. Consistent with this, signatures of directional transmission have been found for bacterial symbionts among co-occurring rodent host species [12,19]. We also detected several viruses in multiple host species, which is consistent with trends indicating that viruses exhibit less host specificity than bacterial symbionts [31].…”
Section: Patterns Of Viral Assemblage Structuresupporting
confidence: 89%
“…For example, targeted assays of known rodent-associated bacterial and viral pathogens such as Bartonella [12,15], Rickettsia [15], Hantaviruses [15] and lymphocytic choriomeningitis virus (LCMV) [16,17] provide evidence of infection hotspots. Targeted assays of known pathogens like Leptospira also have demonstrated that infection prevalence can parallel external factors like physiography and host co-occurrence [11,[17][18][19]. Notably, exploratory surveys (e.g., unbiased metagenomic assays) have demonstrated that urban rodents can host more microbial and viral diversity than anticipated [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, context and scale are critical components in predicting how relative changes in species diversity will alter pathogen transmission. In this issue of Molecular Ecology, Peterson et al (2021) examined abundance and composition of rodent communities in a highly disturbed landscape and found that Leptospira infection prevalence was actually higher at sites where rodent diversity was greatest. In addition to exotic urban species (Figure 1), additional rodent species found at unmanaged vegetated sites are native and have lower competence as pathogen reservoirs.…”
mentioning
confidence: 99%
“…This is a Perspectives essay-data are associated withPeterson et al 2021, to be published concurrently. Uneven investment in post-Katrina recovery has left some neighborhoods abandoned and overgrown [Colour figure can be viewed at wileyonlinelibrary.com]…”
mentioning
confidence: 99%